Photodynamic Antibacterial \(β\)-Cyclodextrin-Modified Cotton Fabric for Medical Applications - Helen Beraldo Firmino; Emilly Karoline Tonini Silva Volante; Ana Claudia Pedrozo da Silva; Fabio Alexandre Pereira Scacchetti; Manuel José Lis; Meritxell Martí; Siddanth Saxena; André Luiz Tessaro; Fabrício Maestá Bezerra (Chemistry and Biochemistry: Research Progress Vol. 4, 2025)
The development of medical and hospital textiles is of significant interest, particularly concerning infectious diseases caused by pathogens. Contact with contaminated surfaces can lead to serious illnesses and pose a significant public health problem. The use of cyclodextrins in textiles for the development of biofunctional fabrics represents an interesting alternative for the advancement of dental, medical, and hospital materials. Cyclodextrins can interact with the chemical groups present in cotton fibers, forming a nanostructured surface with specific functional properties, including antibacterial activity. Although there are numerous antibacterial textile finishes, the use of methylene blue as a cyclodextrin host molecule for photodynamic applications in textile materials remains to be investigated. This is because methylene blue is a photosensitive dye capable of generating singlet oxygen (1O2) when illuminated, which inactivates the pathogenic microorganisms that may be present in wounds. The objective of this study was to develop a biofunctionalized and photoactivatable cotton fabric with antimicrobial properties for use in the cosmetic or medical industries. The materials obtained were characterized via scanning electron microscopy (SEM), Fourier transforms infrared spectroscopy with attenuated total reflection (FTIR-ATR), the determination of cotton fabric functionalization dyeing variables, colorimetry, UV-VIS spectrophotometry, degradation of 9,10-anthracenyl-bis (methylene) dimalonic acid (ABDA), photodegradation tests, and microbiological analysis. The antibacterial activity of the functionalized fabrics was evaluated by adopting the AATCC 100-Test Method for Antibacterial Finishes on Textile Materials: Evaluation. The results showed that the textile was functionalized with \(β\)-cyclodextrin, mainly evidenced by the appearance of the band at 1730 cm-1, indicating the formation of the ester group. Thus, when exposed to light, the non-functionalized material showed greater photobleaching, about 60%, compared to the material treated with cyclodextrin. This result was also reflected in the ABDA degradation kinetics, with the treated material showing 592.00% (first phase) and 966.20% (second phase) higher degradation than the untreated sample. Finally, the photodynamic activity was determined based on the antimicrobial properties of the textile, showing a reduction of more than 99% without exposure to light and 100% when exposed to light. Methylene Blue appears to be a promising candidate for use as a photosensitizer in cutaneous antimicrobial treatments. It is believed that this study could open avenues for future research and the development of antimicrobial fabrics, as well as demonstrate the efficiency of the treatment with cyclodextrin in relation to photobleaching.